Korelasi Bahasa dan Pikiran dalam Perspektif Al-Qur’an - Suleman D. Kadir; Muhammad Jundi; Siti Aliyya Laubaha; Ibadurrahman Ali; Muhammad Zikran Adam; Yuslin Kasan (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2022)
Language and thought are two unique things that only humans have and no other creature has when viewed from the perspective of the study of psycholinguistic disciplines. However, long before the discipline of psycholinguistics correlated the two, the Koran as a holy book had indicated through its verses that there were things related to this study. This study aims to discuss the perspective of the Qur'an on the correlation of language and thought. Based on the background of the problem that examines how the correlation between discussion and thought in the perspective of the Koran, the researcher will provide an explanation of the problem. This study uses a qualitative method approach with a library research approach. Because the type of library search approach, an activity describes the problem being studied. The results of this study show that language and thought are always correlated based on the verses that have been sorted, namely QS al-Baqarah verses 31-32, QS Al-Nisa verse 164, QS al-Mulk verse 23, QS Fushshilat verse 53, QS Yunus verse 101, QS al-Ankabut verse 20, QS al-Hajj verse 46.